ASEAN Tourism Forum Efforts to Increase Tourist Visits in Southeast Asia - Putri, Melisa Yuwana; Purnawarman, Andi (Research Horizon, 2024)
This research carries the title "ASEAN Tourism Forum's Efforts to Increase Tourist Visits in Southeast Asia" under the guidance of Mr. Andi Punawarman S. Sos., M. Si International Relations Study Program, Faculty of Social and Political Sciences, Mulawarman University, 2023. This research aims to determine and describe the ASEAN Tourism Forum’s efforts to increase tourist visits in Southeast Asia using the concept of tourism effort and competitiveness. The type of data used secondary data with data collection techniques through literature study. This research uses qualitative data analysis techniques. Based on research conducted by the author, the research results found that the ASEAN Tourism Forum’s has attempted to increase tourist visits in Southeast Asia by improve tourism services and conduciveness in Southeast Asia, improve international standard tourism services, improve tourism marketing and promotion, create sustainable tourism regulation, develop tourism infrastructure and connectivity and encourage the utilization of the potential nature and cultural resources for tourism.